Game Changer? The Impact of the Reentry Movement on Post-Prison Supervision - Lucken, Karol (Criminal justice policy review, 2020)
Prisoner reentry has been a dominant focus of correctional policy for roughly 2 decades. The strong current of reform that underlays this policy focus means that present correctional practices and conditions should be noticeably different than previous ones. An area where change should be readily observable is in pivotal reentry environments, such as post-prison supervision (PPS). Whereas the reentry literature has concentrated on documenting offender needs, promoting certain strategies, and evaluating the effects of interventions or variables on post-prison recidivism, the current study aims to document the sorts of changes, if any, that have occurred in PPS practice. The impact of the reentry movement on PPS is measured using statewide survey data from 286 PPS professionals with The Florida Department of Corrections. Perceptions of the movement’s impact on supervision emphasis, workplace roles and responsibilities, and resource allocation for services for returning offenders are examined.